Digital Footprint of Consumer Preference: Google Trends Analysis of Halal Cosmetics Market Trends in Indonesia - Kharisma Azza Dzilnurfithry; Dika Jatnika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research investigates the digital footprint of consumer preferences by analyzing halal cosmetic market trends in Indonesia through five-year Google Trends time-series data. Using Korean cosmetics as a global benchmark, the study employs a stepwise quantitative methodology that integrates slope calculations grounded in the Theory of Planned Behavior (TPB) and quadrant analysis based on Segmenting, Targeting, and Positioning (STP) strategies. The findings reveal that halal cosmetics exhibit greater consumer interest stability with an aggregate slope of -0.08, compared to -0.31 for Korean skincare. Furthermore, the quadrant analysis successfully categorizes regional segments into Hybrid, Trend-Driven, Low-Involvement, and Conscious markets. The study concludes that the integration of slope parameters and spatial segmentation effectively captures market dynamics, providing a robust strategic foundation for optimizing halal cosmetic marketing tailored to the specific preference characteristics of diverse Indonesian regions.